Hyperventilation in Children with Dengue Hemorrhagic Fever (DHF) - Kasim Y. A.; Anky Tri Rini K. E.; Sumarmo S. P. S. (Indonesian Pediatric Society Publishing House, 2019)
Many studies of Dengue Hemorrhagic Fever (DHF) have been done but only a few revealed the respiratory status. Respiratory problems arise. because of plasma leakage through the 'damaged capillaries, causing lung edema and in turn result in hypoxemia. This later on will be compensated by a hyperventilation state. During a 6-month-period (May to September 1988), two aspects were studied in 85 patients hospitalized with DHF. First, the ventilatory pattern and second, the result of giving oxygen support in improving the respiratory disturbance, in this case alveolar hyperventilation. The incidence of alveolar hyperventilation in DHF grade II (DHF II) and Dengue Shock Syndrome (DSS) differed significantly. Hypoxemia occurred in DHF II and DSS with no significant differences. The difference of the incidence of metabolic acidosis in DHF II and DSS were significant. In DHF II patients having had hyperventilation state, oxygen therapy decreased respiration rate significantly and increased the PaC02 though not significantly.